Host Nonresponsiveness Does not Interfere With Vaccine‐Mediated Protection Against Gastric Helicobacter Infection. Issue 3 (15th February 2015) - Harbour, Stacey N.; Mitchell, Hazel M.; Sutton, Philip
Abstract Background Helicobacter pylori pathogenesis results from the inflammation induced by chronic infection. CBA mice are nonresponsive to gastric Helicobacter infection, providing a useful model for examining host regulation of Helicobacter‐induced gastritis. We examined whether gastric Helicobacter nonresponsiveness impacts upon vaccine efficacy and whether immune‐mediated protection could occur in the absence of inflammation. Methods Mice were vaccinated prior to challenge with Helicobacter felis or H. pylori. Gastritis and H. felis colonization was evaluated histologically. H. pylori colonization was quantified by colony‐forming assay. Results Immunizations protected CBA mice against challenge with either H. felis or H. pylori. Protection against H. felis was marked by a loss of nonresponsiveness and development of an atrophic gastritis with mucus metaplasia. However, vaccine‐induced protection against H. pylori was only associated with cell infiltration into the gastric mucosa. Conclusions Nonresponsiveness to gastric Helicobacter infection did not interfere with vaccination‐induced protection. Vaccine‐induced protective immunity against H. pylori was linked with the induction of cellular infiltration, but importantly not atrophic gastritis.